2022
DOI: 10.1182/bloodadvances.2021006752
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of suicidal ideation in a series of patients with sickle cell disease after hematopoietic stem cell transplantation

Abstract: Conflict of interest: No COI declared COI notes: Preprint server: No; Author contributions and disclosures: ADM designed the research and wrote the paper SGC managed the data and did the analysis AH participated in background research and writing the paper EJL did data collection SMD did data collection MYM participated in data analysis, interpretation, and writing the paper Non-author contributions and disclosures: No;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…There are no studies of psychiatric outcomes for adult patients with SCD undergoing HCT. Some of our authors (ADM, EJL and MYM) found a 43% rate of suicidal ideation in the year post‐transplant in a 14‐patient case series 214 . Others have found ongoing daily pain, fatigue, anxiety and depressed mood in patients with SCD recovering from HCT 82 .…”
Section: Considerations For Medical Comorbidities Of Sickle Cell Diseasementioning
confidence: 74%
See 1 more Smart Citation
“…There are no studies of psychiatric outcomes for adult patients with SCD undergoing HCT. Some of our authors (ADM, EJL and MYM) found a 43% rate of suicidal ideation in the year post‐transplant in a 14‐patient case series 214 . Others have found ongoing daily pain, fatigue, anxiety and depressed mood in patients with SCD recovering from HCT 82 .…”
Section: Considerations For Medical Comorbidities Of Sickle Cell Diseasementioning
confidence: 74%
“…Some of our authors (ADM, EJL and MYM) found a 43% rate of suicidal ideation in the year post-transplant in a 14-patient case series. 214 Others have found ongoing daily pain, fatigue, anxiety and depressed mood in patients with SCD recovering from HCT. 82 Studies of the prevalence of specific psychiatric diagnoses, clinical evaluations and potential interventions are needed for this population.…”
Section: Conside R Ations For M E Dica L Comor Biditi E S Of Sick L E...mentioning
confidence: 99%